2019
DOI: 10.3390/insects11010012
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Delivery of dsRNA and DNA in Cultured Silkworm Cells for Gene Function Analysis Using PAMAM Dendrimers System

Abstract: Polyamidoamine (PAMAM) dendrimers are emerging as intriguing nanovectors for nucleic acid delivery because of their unique well-defined architecture and high binding capacity, which have been broadly applied in DNA-and RNA-based therapeutics. The low-cost and high-efficiency of PAMAM dendrimers relative to traditional liposomal transfection reagents also promote their application in gene function analysis. In this study, we first investigated the potential use of a PAMAM system in the silkworm model insect. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…[ 146 ] Currently, the ability of vectors such as PAMAM dendrimers to deliver RNA to tumor cells has been well established. [ 147 ] Multiple in vivo and in vitro studies have proved that PAMAM dendrimers can successfully deliver genetic material (siRNA, miRNA, and plasmids) into cells and produce specific therapeutic effects, [ 130 ] such as silencing some protein genes and inhibiting the proliferation of tumor cells.…”
Section: Utilization Of Dendrimers In Cancermentioning
confidence: 99%
“…[ 146 ] Currently, the ability of vectors such as PAMAM dendrimers to deliver RNA to tumor cells has been well established. [ 147 ] Multiple in vivo and in vitro studies have proved that PAMAM dendrimers can successfully deliver genetic material (siRNA, miRNA, and plasmids) into cells and produce specific therapeutic effects, [ 130 ] such as silencing some protein genes and inhibiting the proliferation of tumor cells.…”
Section: Utilization Of Dendrimers In Cancermentioning
confidence: 99%
“…The dsRNAs for control gene of Red were also synthesized. G5-PAMAMmediated delivery of dsRNA was used according to the previous protocol (45). G5-PAMAM was purchased from Chenyuan Company (Shandong, China).…”
Section: Rna Interferencementioning
confidence: 99%
“…We firstly synthesized specific dsRNAs against ORF and UTR of BmTCTP (referred to as dsTCTP-ORF and dsTCTP-UTR) (Figure 2A). G5-PAMAM system was used to deliver dsRNAs of BmTCTP into the BmN cells to silence BmTCTP expression (45). RT-PCR result showed that both dsTCTP-ORF and dsTCTP-UTR were able to decrease the mRNA transcription of BmTCTP compared with the dsRed control treatment (Figure 2B), and also dsTCTP-ORF could specifically decrease the expression of FLAG-TCTP by immunoblotting (Figure S1), which together revealed that dsRNAs of BmTCTP could efficiently silence its own expression.…”
Section: Bmtctp Knockdown Promoted Viral Replicationmentioning
confidence: 99%
“…To address this challenge, a variety of delivery approaches have been developed by multidisciplinary research communities, including physical (thermoporation, electroporation, magnetoporation, mechanoporation, optoporation, sonoporation, and microinjection) strategies (Meacham et al., 2014 ; Du et al., 2018 ), chemical strategies (artificial lipids (Hou et al., 2022 ), dendrimers (Lu et al., 2019 ), polymers (Farshbaf et al., 2018 ), carbon nanotubes (Mangla et al., 2020 ) or nanoparticles and direct chemical modification such as PLGA (Matta & Maalouf, 2019 ) or cholesterol (Ruwizhi & Aderibigbe, 2020 )), and biological strategies (viral delivery (Lundstrom, 2020 ) and non-viral delivery (Bono et al., 2020 ) such as cell penetrating peptides (CPPs)) (Thompson et al., 2012 ; Liu et al., 2016 ; Geng et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%